MHD stagnation point flow over a stretching cylinder with variable thermal conductivity and joule heating - Jahan, S. (American Institute of Physics Inc., 2016)
The behavior of magnetohydrodynamics (MHD) flow of viscous fluid near the stagnation point over a stretching cylinder with variable thermal conductivity is analyzed. Thermal conductivity is assumed to be linearly related with temperature. The joule heating effects due to magnetic field is also encountered here. Analytical solutions are developed for both momentum and energy equations by using the homotopy analysis method (HAM). The variations of different parameters on the velocity and temperature distributions along with the skin friction coefficient and local Nusselt number are displayed graphically. Numerical values for the skin friction coefficient are calculated and discussed. Â© 2016 Author(s).